A comparative analysis of milling strategies of complex geometry surfaces - Globocki-Lakić Gordana; Sredanović B.; Jotić G.; Gotovac S. (FME Transactions, 2022)
This paper analyses the influence of machining strategies and cutting parameters on the milling of aluminium complex geometry parts. In the first experimental phase, parts were machined with a combination of two roughing strategies and three finishing strategies, with recommended machining parameters. The machining time, machining surface roughness, and the surface geometric accuracy were measured. In the second phase, a new sample was machined with corrected cutting parameters using the best strategy adopted from the first phase. The results have shown that the selection of machining strategy and cutting parameters significantly affects the productivity, quality, and accuracy when machining complex geometry parts.